Identifikasi Gugus SiHx (x=1, 2 dan 3) pada Silikon Berpori dari Substrat Si (111) Tipe-P - I Nyoman Sudiana (Lambung Mangkurat University Press, 2010)
The study of identification of functional group SiHx (x=1, 2, 3) to typepSi (111) made by anodizatied silicon wafer in 0,3 ohm-cm hydrofluoric (HF) hasbeen conducted. The objective of the research is to determine the effects of HFconcentrations and anodization time on PS functional groups. HF concentrationwas varied to 10%, 20%, 30% and 40% the anodization time was varied to 10,20, 40 and 60 minutes respectly. While the anodization it was used a magneticstirrer to keep the homogenity of the solution. The existence of SiH groups ischaracterized by FTIR spectrofotometer. The results shows that SiH groupfunctional appears around absorbtion area of 2112-2100 cm-1, 920-890 cm-1and 856 cm-1. Where as the longer time anodization the fewer of SiH groupsformed.